Analisa Perawatan Central Vein Catheter (CVC) Terhadap Kejadian Infeksi Aliran Darah Primer (IADP) Pada Pasien Di Ruang Intensive Rumah Sakit Umum Daerah Dr. Zainoel Abidin Banda Aceh - Rikanurrizki, Rikanurrizki; Fatmi, Elizar; Zulfan, Muhammad (LITBANG RSUDZA, 2024)
Primary bloodstream infection is a laboratory-confirmed bloodstream infection that cannot be attributed to any source other than a Central Vein Catheter (CVC) and develops 48 hours after placement. Central Vein Catheter (CVC) placement in critical patients is often necessary for measuring central venous pressure, fluid resuscitation, and administration of inotropic and vasoactive drugs. This study aimed to determine the correlation between CVC care and patient-related risk factors for the incidence of primary bloodstream infection in patients in the Intensive Care Unit of Dr. Zainoel Abidin Regional General Hospital. The study employed a quantitative design with a cross-sectional study approach, and samples were selected using accidental sampling. Bivariate data analysis was conducted using the chi-square test, while multivariate data analysis used logistic regression with backward method modeling. The study identified age (p=0.018), underlying disease (p=0.017), and CVC care (p=0.019) as factors associated with the incidence of primary bloodstream infection. The underlying disease was the most dominant factor affecting the incidence of primary bloodstream infection, with EXP (B) = 23.293.